Healthcare-seeking behaviour among clinic-based tuberculosis patients - Zacheus Matebsi; Herman Meulemans; Christiane Timmerman (Acta Academica, 2005)
This study investigated the factors influencing recourse to healthcare in a sample of 220 tuberculosis (TB) patients. Data collection was by means of face-to-face interviews. Patients sought help mainly from primary healthcare clinics (46%) and private doctors (40%). The mean patient delay was seven weeks, with only 21% of patients seeking professional healthcare within less than two weeks. The results show that lack of awareness of TB and use of a home remedy were significantly associated with a delay of longer than two weeks in seeking healthcare. These findings indicate an urgent need to educate communities on the signs and symptoms of TB, as well as the need to  attend designated health facilities for early diagnosis and proper treatment.